Petrology and hydrocarbon significance of the coaly source rocks from the Pinghu Formation in the Xihu Sag, East China Sea Shelf Basin. Issue 5 (September 2020) - Liu, Jinshui; Kang, Shilong; Shen, Wenchao; Qin, Lanzhi; Zhou, Qianyu; Li, Shuxia; Ding, Fei; Shao, Longyi
The Xihu Sag in the East China Sea Shelf Basin contains abundant oil and gas reserves and is a focus for hydrocarbon exploration and development. Source rocks are mainly coals and coal-measures mudstones in the Paleogene Pinghu and Huagang formations. Samples from the Pinghu Formation in the Xihu Sag were collected for petrology, total organic carbon, and Rock-Eval analysis for the purpose of investigating macerals component and their contributions to hydrocarbon generation potential. The coaly source rocks from the Pinghu Formation are dominated by vitrinite (average 86.18%) but have an obviously elevated content of liptinite (average 12.59%) and a much lower amount of inertinite (average 1.23%). Liptinite of the samples is mainly composed of resinite, with a small amount of cutinite, sporinite and alginate in descending order. TOC values are 37.55%–65.58% (average 49.16%). Effective HI values are 167–281 mg HC/g TOC (average 223.5 mg HC/g TOC), suggesting the organic matter is type II kerogen. Relatively high HI values and macerals components suggest that the coaly source rocks can generate both oil and gas. Although the liptinite in the coaly source rocks has a content lower than vitrinite values, it makes a significant contribution to both total hydrocarbon and liquid hydrocarbon generation. The contributions of vitrinite, liptinite and inertinite to the total hydrocarbon generation approximately are 63.21%, 36.46% and 0.33%, respectively. The contributions of vitrinite and liptinite to the liquid hydrocarbon generation are approximately 40.95% and 59.05%, respectively. These results demonstrate that the coaly source rocks are dominated by vitrinite macerals with a relatively higher content of liptinite macerals, especially resinite, and these source rocks are more prone to both total hydrocarbon and liquid hydrocarbon generation. Paleogene coaly source rocks from other parts of the world should be considered for their oil-prone nature.